Lysophosphatidic acid induces tumor necrosis factor‐alpha to regulate a pro‐inflammatory cytokine network in ovarian cancer. Issue 10 (26th August 2020) - Wang, Wei; Wu, Jinhua; Mukherjee, Abir; He, Tianhai; Wang, Xiang‐Yang; Ma, Yibao; Fang, Xianjun
Abstract: Epithelial ovarian carcinoma tissues express high levels of tumor necrosis factor‐alpha (TNF‐α) and other inflammatory cytokines. The underlying mechanism leading to the abnormal TNF‐α expression in ovarian cancer remains poorly understood. In the current study, we demonstrated that lysophosphatidic acid (LPA), a lipid mediator present in ascites of ovarian cancer patients, induced expression of TNF‐α mRNA and release of TNF‐α protein in ovarian cancer cells. LPA also induced expression of interleukin‐1β (IL‐1β) mRNA but no significant increase in IL‐1β protein was detected. LPA enhanced TNF‐α mRNA through NF‐κB‐mediated transcriptional activation. Inactivation of ADAM17, a disintegrin and metalloproteinase, with a specific inhibitor TMI‐1 or by shRNA knockdown prevented ovarian cancer cells from releasing TNF‐α protein in response to LPA, indicating that LPA‐mediated TNF‐α production relies on both transcriptional upregulations of the TNF‐α gene and the activity of ADAM17, the membrane‐associated TNF‐α‐converting enzyme. Like many other biological responses to LPA, induction of TNF‐α by LPA also depended on the transactivation of the epidermal growth factor receptor (EGFR). Interestingly, our results revealed that ADAM17 was also the shedding protease responsible for the transactivation of EGFR by LPA in ovarian cancer cells. To explore the biological outcomes of LPA‐induced TNF‐α, we examined the effects of a TNF‐α neutralizing antibody and recombinant TNF‐α soluble receptor on LPA‐stimulated expression of pro‐tumorigenic cytokines and chemokines overexpressed in ovarian cancer. Blockade of TNF‐α signaling significantly reduced the production of IL‐8, IL‐6, and CXCL1, suggesting a hierarchy of mechanisms contributing to the robust expression of the inflammatory mediators in response to LPA in ovarian cancer cells. In contrast, TNF‐α inhibition did not affect LPA‐dependent cell proliferation. Taken together, our results establish that the bioactive lipid LPA drives the expression of TNF‐α to regulate an inflammatory network in ovarian cancer.